Relationship between Talent Management and Labour Turnover in Nigerian Banking Sector - Kadiri, Ismaila Bolarinwa; Isiaka, Sulu Babaita; Jimoh, Adams Lukman (NIU Journal of Humanities, 2018)
Employees in Nigeria banking system are highly pressured to improve their present performance while little or no room is given for development of talent to improve future performance. This pressure is what brings about job insecurity, absenteeism, burnout and resignation. This study therefore examined the relationship between talent management and labour turnover in the Nigerian banking sector.  A total of 320 respondents were chosen for the study using stratified sampling technique and 178 sampling size was determined through the use of Yaro Yamane formula. Primary data was collected through questionnaire. The Statistical instrument used in analyzing the data and testing the Hypotheses formulated were the Statistical Package for Social Sciences and  Pearson Product Moment Correlation analysis respectively. The result shows that there is a positive and significant relationship between Talent Management and Labour Turnover. (r =.620, p < .001). The conclusion reached is that this study affirms that talent management and employee turnover is positively related and significant to banks performance. It was recommended that organizations should ensure effective and efficient staffing process that will ensure that the right talent is recruited and appropriately placed to ensure reduction in employee turnover.